4 - District Assemblies in a Fix: The Perils of Self-Seeking Tendencies in Decentralisation Policy Reforms in Malawi - Chinsinga, Blessings (Africa Development, 2007)
This article appraises the prospects of the District Assembly system inaugu- rated under the auspices of decentralisation policy reforms introduced to insti- tutionalise local governance structures and processes that are responsive, demo- cratic, and capable of improving the livelihoods of the poor. While there seems to be reasonable consensus about the desirability of a decentralised planning framework as a vehicle for sustainable governance, development and poverty reduction, most stakeholders are nevertheless primarily motivated by the desire to advance, safeguard and gratify self-interests. Therefore, the major thrust of the argument of this paper is that unless these self-seeking tendencies are effec- tively tamed, the trinity of good governance, development and poverty reduc- tion in the evolving structures and processes of local government will remain an unattainable ideal.